Asymmetric return and volatility transmission in conventional and Islamic equities - Zaghum Umar; Tahir Suleman (Risks, 2017)
This paper analyses the interdependence between Islamic and conventional equities by taking into consideration the asymmetric effect of return and volatility transmission. We empirically investigate the decoupling hypothesis of Islamic and conventional equities and the potential contagion effect. We analyse the intra-market and inter-market spillover among Islamic and conventional equities across three major markets: the USA, the United Kingdom and Japan. Our sample period ranges from 1996 to 2015. In addition, we segregate our sample period into three sub-periods covering prior to the 2007 financial crisis, the crisis period and the post-crisis period. We find weak support for the decoupling hypothesis during the post-crisis period.
Keywords: G01; G10; G15; 330; Islamic stock market; conventional stock markets; asymmetric return and volatility spillovers; EGARCH